Syaikh Muhammad Abduh:: Gagasan Pembaharuannya Dalam Pendidikan Islam - Ifendi, Mahfud; Munziah, Munziah (Jurnal Man-anaa, 2024)
Muhammad Abduh was concerned about the stagnation of the Muslim world. He became a leader in modernizing Islamic education. He believed that this was the key to reviving Muslim glory. He did this by implementing reforms that had never been done before. This research explores Abduh's innovative ideas and actions in reforming the education system and highlights their continued relevance in today's world. Concerning the existing literature, the type of research used in writing this article is library research using a descriptive-qualitative approach. The enduring significance of Abduh's thoughts is: 1) Bridging the knowledge gap, he emphasized the integration of general knowledge with religious studies in Islamic education. 2) Holistic development, he advocates education that covers all aspects - cognitive (thinking), affective (values) and psychomotor (skills) - for well-rounded individuals. 3) Active learner, seeking student participation and the development of higher-order thinking skills. 4) Student-centred approach, he emphasizes the importance of considering students' psychology and individual needs in the learning process. Abduh's vision serves as a beacon for modernizing Islamic education in today's world. His progressive ideas provide a strong foundation for cultivating future generations of faith and knowledge. Ultimately, this will contribute to the progress of Muslim society and civilization.